Publicity of Subordinate Legislation in Nigeria: An Appraisal - Ijaiya, N. O. A. (NIU Journal of Humanities, 2018)
The term `subordinate legislation` has been variously described as subsidiary legislation, delegated legislation, administrative rule making et. cetera . In Nigeria, section 4 of the 1979 constitution vested the Federal and State legislative powers in the National Assembly and State House of Assembly respectively.  An Act or act traceable to either of these bodies is regarded as a valid legislative one.  During Military regime with the enactment of the constitution (suspension and modification Decree) `the power to make laws for the peace, order and good government of Nigeria or any part thereof with respect to any matter what whatsoever` was vested in the Federal Military Government. This power was to be exercised by means of Decree signed by the Head of the Federal Military Government while that of the State was exercised by means of Edicts signed by the State Military Governor.  In 1999 there was another Military take over that enacted the Constitution (Suspension and Modification) Amendment Decree of 1985.  This decree substantially in corporate Decree No. 1 of 1984 and the major charge which was introduced was in respect of the title of the signatory of Decree. Instead of the head of the Federal Military Government, it was the President, Commander-in-Chief of the Armed Forces.  The exercise of all legislative powers was vested in the Armed Forces Ruling Council which is the highest ruling Military body. This paper therefore addresses itself to the requirements for publication of laws made by persons other than the Legislature in Nigeria.